Investment Knowledge, Income, Risk, and Gold Price Effects on Gen Z's Gold Investment Interest with Trust Moderation - Indra Yanti Yanti; Jumawan Jasman; Nispa Sari (BIMA Journal (Business, Management, & Accounting Journal), 2026)
The development of technology has facilitated access to investment information; however, public interest and participation in investment, particularly gold investment, remain relatively low. Purpose: This study aims to analyse the influence of investment knowledge, income, risk perception, and gold price fluctuation on gold investment interest among Generation Z, with trust as a moderating variable. Methodology: This study employs a quantitative approach. The population consists of Generation Z individuals in North Luwu Regency. The sampling technique uses non-probability sampling with purposive sampling, and respondents were selected using accidental sampling, resulting in 247 respondents. Data were analysed using SmartPLS with the Structural Equation Modelling (SEM) approach based on Partial Least Squares (PLS). Results: The results indicate that investment knowledge has a positive and significant effect on gold investment interest. Meanwhile, income, risk perception, and gold price fluctuation do not have a significant effect. In the moderation test, trust does not moderate the relationship between investment knowledge and investment interest but significantly moderates the relationship between income and investment interest. Findings: This study reveals that investment knowledge is the most dominant factor influencing gold investment interest among Generation Z. Additionally, trust plays an important role in strengthening the relationship between income and investment interest. Novelty: The novelty of this research lies in the inclusion of trust as a moderating variable in the relationship between economic and psychological factors and investment interest. Originality: This study integrates economic and psychological factors by incorporating trust as a moderating variable in Generation Z’s gold investment behaviour. Conclusion: Investment knowledge is the main factor influencing gold investment interest, while trust strengthens the effect of income on investment interest. Type of Paper: Empirical research paper.